Efetividade da cinoterapia para sinais e sintomas dos transtornos mentais de pessoas adultas e idosas assistidas em ambientes sociais e de saúde: revisão sistemática e metanálise - Paludett, Marcos Vinícius Nunes (2025)
Contextualization: dogs represent a life support for people with limitations or special needs, as well as strengthening therapeutic healthcare environments. Objective: to evaluate the effectiveness of canine therapy for signs and symptoms resulting from mental disorders in adults and elderly people assisted in social and health environments, compared to control groups (usual treatment and/or without intervention). Method: Systematic effectiveness review based on the JBI. Randomized controlled trials (RCTs) using canine therapy as an intervention for signs and symptoms of mental disorders were included. A search was conducted in eight information sources. Screening and selection, extraction, and risk of bias assessment were performed in a double-independent manner. Narrative synthesis and pairwise meta-analysis were performed. Results: 3,079 references were analyzed, and 40 comprised the corpus of this review. Most RCTs were at moderate to low risk of bias. Canine therapy reduces symptoms related to depression in dementia (CI: -5.25, -3.12) and trait anxiety (CI: -9.99, -4.57), compared to control groups. For neuropsychiatric symptoms in people with dementia, control is more effective (CI: 0.92, 2.21). Other RCTs reveal contributions of the practice to psychotic behaviors, stress reduction, well-being, communication, cognition, agitation, mood, depressive state, alertness, reduced isolation, and self-judgment. Conclusion: Canine therapy reduces symptoms related to depression in dementia and trait anxiety. However, for neuropsychiatric symptoms in people with dementia, standard treatment is more effective. There is evidence of benefits from the practice for signs and symptoms related to schizophrenia, dementia, Alzheimer's, autism spectrum disorder, post-traumatic stress disorder, and substance use disorders. However, there is high heterogeneity and very low certainty of evidence, so the findings need to be interpreted with caution and considering the limitations of primary research.